sea grasses - novel marine nutraceuticals - N. PUSHPA BHARATHI,; P. AMUDHA,; V. VANITHA, (International Journal of Pharma and Bio Sciences, 2016)
Marine plants are known to produce a large number of structurally diverse secondary metabolites. They are found to be economically important in the field of food additives, nutraceutical and drugs. Seagrasses are a paraphyletic group of marine hydrophilus angiosperms, which evolved three to four times from land plants back to the sea. It lives in an estuarine or in the marine environment, and nowhere else.Seagrasses contain several compounds in their secondary metabolism in which they differ from terrestrial plants. They produce novel chemicals to withstand extreme variations in pressure, salinity, temperature, and so forth, prevailing in their environment, and the chemicals produced are unique in diversity, structural, and functional.The phytochemical present in seagrasses exhibit antibacterial, antioxidant, antitumor activity.New inclination in the field of drug discovery from natural sources highlights on the investigation of the marine ecosystem to survey numerous complex and novel chemical entities. These entities are the source of new lead form treatment of many diseases such as cancer, AIDS, inflammatory condition, arthritis, malaria and large variety of viral, bacterial, fungal diseases. Several species of sea grasses are used as human food or as raw material for the production of compounds of nutritional interest. Compared to algae, sea grasses remain less exploited despite the fact that they offer tremendous opportunities to find new commercially valuable phytochemicals. Therefore, their metabolite contents constitute another treasure of the ocean which is hidden. This paper gives an overall view on their nutraceutical activity and their potential as anticancer agent so that the hidden facts will be explored to provide a new cheap source for therapeutically and nutraceutical application. Thus, it is evident from various literature that sea grasses could be used as a potential source for natural health product.